Human articular cartilage mechanosensitivity is related to histological degeneration – a functional MRI study. Issue 11 (November 2019) - Nebelung, S.; Post, M.; Knobe, M.; Shah, D.; Schleich, C.; Hitpass, L.; Kuhl, C.; Thüring, J.; Truhn, D.
Summary: Objective: To investigate changes in response to sequential pressure-controlled loading and unloading in human articular cartilage of variable histological degeneration using serial T1ρ mapping. Method: We obtained 42 cartilage samples of variable degeneration from the medial femoral condyles of 42 patients undergoing total knee replacement. Samples were placed in a standardized artificial knee joint within an MRI-compatible whole knee-joint compressive loading device and imaged before (δ0 ), during (δld1, δld2, δld3, δld4, δld5 ) and after (δrl1, δrl2, δrl3, δrl4, δrl5 ) pressure-controlled loading to 0.663 ± 0.021 kN (94% body weight) using serial T1ρ mapping (spin-lock multigradient echo sequence; 3.0T MRI system [Achieva, Philips]). Reference assessment included histology (Mankin scoring) and conventional biomechanics (Tangent stiffness). We dichotomized sample into intact ( n  = 21) and degenerative ( n  = 21) based on histology and analyzed data using Mann Whitney, Kruskal Wallis, one-way ANOVA tests and Spearman's correlation, respectively. Results: At δ0, we found no significant differences between intact and degenerative samples, while the response-to-loading patterns were distinctly different. In intact samples, T1ρ increases were consistent and non-significant, while in degenerative samples, T1ρ increases were significantly higher ( P  = 0.004, δ0 vs δld1, δ0 vs δld3), yet undulating and variable. With unloading, T1ρ increases subsided, yet were persistently elevated beyond δ0. Conclusion: Cartilage mechanosensitivity is related to histological degeneration and assessable by serial T1ρ mapping. Unloaded, T1ρ characteristics are not significantly different in intact vs degenerative cartilage, while load bearing is organized in intact cartilage and disorganized in degenerative cartilage.